SLAVERNES SLÆGT: Slægtshistorie som personlig fortælling og kritisk diskurs - Frello, Brigitta (Tidsskriftet Antropologi, 2004)
The empirical focus of the article is on the serial, Slaves in the Family, which the Danish TV channel, DR2, launched in January 2005. It is a serial of four programs on Scandinavian descendants of slaves primarily from the former Danish colony of the West Indies: St. John, St. Thomas and St. Croix. This serial is analysed with special reference to the ways in which kinship is represented and the implications of these forms of representation. The first part of the analysis focuses on three specific narratives of kinship, which are presented during the serial. The question is how the participants individually make sense of their consanguinity with slaves. The second part of the analysis focuses on the serial’s overall narrative and the consequences, which the choice of ‘kinship’ as a narrative device has for the construction of the story. It is argued that the serial, by telling this story through the lens of kinship, partly undermines its own proclaimed critical perspective. Rather than being a story of re-viewing history and claiming responsibility for the atrocities, which were committed by the Danish state and by other Danish agencies during colonial time, it becomes a story of re-uniting family bonds which have been unrightfully torn apart. By this move, the categorical distinction between white and black, Scandinavian and African, master and slave, is denied, rather than transgressed and the potentially subversive story of the hybrid descent of the Danes is displaced by a sentimental quest for a ‘true’ personal identity.